가미계격탕과 독소루비신 조합의 비소세포성폐암주에서 소포체스트레스에 의한 상승적 세포사멸효과 - 황성민; Sung Min Hwang; 박수연; Su Yeon Park; 심덕용; Deok Yong Sim; 김준성; Jun Sung Kim; 심범상; Bum Sang Shim; 김봉이; Bong Lee Kim; et al. (大韓本草學會誌, 2025)
Objectives : Despite previous evidence on antiangiogenic, antimetastatic, immunomodulatory and apoptotic effect of Ka-mi-kae-kyuk-tang (KMKKT) in prostate and lung cancers, the underlying antitumor mechanism and clinical application of KMKKT is not fully understood to date. Hence, in the current work the synergistic antitumor pathogenesis of Ka-mi-kae-kyuk-tang (KMKKT) and doxorubicin was explored in non small cell lung cancer (NSCLC) cells. Methods : MTT assay for cytotoxicity, terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay. cell cycle analysis, RNA interference and Western blotting were employed in this project. Results : Combination of KMKKT and Doxorubicin showed synergistic cytotoxicity in A549 and HCC827 cells better than in H460 and PC-9 cells. Also, Combination significantly augmented sub G1 population and the number of TUNEL positive cells compared to KMKKT or Doxorubicin control alone. Consistently, Combination enhanced poly(ADP-ribose) polymerase(PARP) cleavage and Bax activation, suppressed the expression of cyclin D1, Mcl-1 and Bcl-2 and also induced endoplasmic reticulum (ER) stress proteins such as CCAAT/-enhancer-binding protein homologous protein (CHOP), activating transcription factor 4 (ATF4), Erol-Lα, the inositol-requiring protein 1 α (IRE1 α) and glucose-regulated protein 78 (GRP78 in A549 and HCC827 cells. Conversely, depletion of CHOP reversed the ability of Combination to exert cytotoxicity, cleave PARP and caspase 3 and increase sub G1 population in A549 and HCC827 cells. Conclusion : Our findings suggest that KMKKT has potential to enhance antitumor activity with Doxorubicin in NSCLCs via ER stress mediated apoptosis induction.